The effect of resistance exercises using additional weights on some physical abilities and improving performance in free swimming for female students (Journal of the College of Basic Education, 2022)
The first chapter included the introduction of the research and its importance, as the researcher mentioned that swimming is one of the popular, exciting and enjoyable sports in many countries of the world because of its importance that distinguishes it from other sports, as it gives people physical, health, psychological and social benefits, and swimming is like any other sport based on some The basic skills that together form the basic movements of the swimmer's movement in the water, and learning them is the basis for practicing all water sports.